2012
DOI: 10.1586/ern.11.183
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutic avenues to tackle social cognition problems in schizophrenia

Abstract: Therapeutic strategies for improving social cognition in patients with schizophrenia have shown much promise in improving social functioning, as well as remediating core psychotic symptoms. However, the efficacy of previous interventions has often been limited by the ambiguity and inconsistency of the categorized subdomains of social cognition, including theory of mind, emotion processing, social perception and attributional bias. Recent research in social and cognitive neuroscience has revealed many new issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 121 publications
0
14
0
4
Order By: Relevance
“…Contrary to our hypothesis, we did not find a relationship between oxidative stress biomarkers and social cognition. Although neurocognitive deficits in schizophrenia explain some variance of social cognitive deficits, a substantial number of studies have demonstrated the independent role of social cognition in symptom severity, social functioning and quality of life in schizophrenia patients (reviewed in [ 33 ]). Furthermore, many studies have successfully identified a separate function for different subdomains of social cognition [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to our hypothesis, we did not find a relationship between oxidative stress biomarkers and social cognition. Although neurocognitive deficits in schizophrenia explain some variance of social cognitive deficits, a substantial number of studies have demonstrated the independent role of social cognition in symptom severity, social functioning and quality of life in schizophrenia patients (reviewed in [ 33 ]). Furthermore, many studies have successfully identified a separate function for different subdomains of social cognition [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Social cognition denotes the ability to process, assimilate and respond to social stimuli, and can be categorized into several domains that work at different levels; from basic low-level emotion perception, to theory of mind (i.e. to attribute and understand the mental states of others, such as beliefs and intentions) up to appropriate behavioral responses [ 33 ]. Additionally, social cognitive deficits have been linked to symptom severity in schizophrenia, and are negatively associated with quality of life and social functioning [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…For this same reason, reliably identified differences among diagnoses may be crucial to pinpoint treatment planning, medication management, and long-term patient care ( 115 ). Establishing differences in social functioning might also be indicative of the likely success of remediation through recent socio-cognitive training schemes that aim to improve abilities, such as theory of mind ( 124 127 ). It has been claimed that socio-cognitive impairments, such as theory of mind, may be less of a determinant of functioning in bipolar disorder than in schizophrenia, and therefore that non -social cognitive remediation may be better suited for bipolar disorder ( 108 ).…”
Section: Comparative Assessments Of Theory Of Mind In Bipolar Disordementioning
confidence: 99%
“…Studies of social cognition in schizophrenia have shown the following: Social cognition predicts functional outcomes independently from, and perhaps more strongly than, neurocognition [15][16][17][18][19][20][21]; social cognition is related to the severity of the disorder and rates of relapse [22][23][24]; negative and disorganized symptoms are related to low social competence, difficulty in social representations, and poor social and vocational adjustment [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]; there is a significant association between social cognition and quality of life (QoL) [26,27]; and social cognitive skills play an important role in patients' subjective evaluation of their own QoL [28]. Finally, as Tas et al [27] recently reported, ''the association between mental state reasoning and the more internal aspect of QoL in schizophrenia may reflect a specific role for social cognition in introspective and subjective judgments of one's own QoL, whereas neurocognition and negative symptomatology may be more predictive of the external or extrinsic aspect of QoL.…”
Section: Introductionmentioning
confidence: 99%